Longitudinal deprivation trajectories and risk of cardiovascular disease in New Zealand. (September 2018) - Shackleton, Nichola; Darlington-Pollock, Frances; Norman, Paul; Jackson, Rodney; Exeter, Daniel John
Abstract: We used longitudinal information on area deprivation status to explore the relationship between residential-deprivation mobility and Cardiovascular Disease (CVD). Data from 2, 418, 397 individuals who were: enrolled in any Primary Health Organisation within New Zealand (NZ) during at least 1 of 34 calendar quarters between 1st January 2006 and 30th June 2014; aged between 30 and 84 years (inclusive) at the start of the study period; had no prior history of CVD; and had recorded address information were analysed. Including a novel trajectory analysis, our findings suggest that movers are healthier than stayers. The deprivation characteristics of the move have a larger impact on the relative risk of CVD for younger movers than for older movers. For older movers any kind of move is associated with a decreased risk of CVD. Highlights: Analysed longitudinal linked anonymised records covering 94% of NZ's adult population. Applied trajectory analysis to analyse patterns of residential deprivation-mobility. On aggregate stayers in deprived areas had the highest risk of a CVD event. There is a moderating effect of age on the relationship between residential deprivation-mobility and CVD.